High-Resolution Respirometry in Diagnostics of Mitochondrial Diseases Caused by Mitochondrial Complex I Deficiency - Krylova, T. D.; Tsygankova, P. G.; Itkis, Y. S.; Sheremet, N. L.; Nevinitsyna, T. A.; Mikhaylova, S. V.; Zakharova, E. Y. (Biochemistry (Moscow). Supplement. Series B, Biomedical chemistry, 2018)
Mitochondrial complex I deficiency (CID) is one of the most common defects in the OXPHOS system; it represents more than 30% cases of mitochondrial diseases. The group is characterized by clinical and genetic heterogeneity and comprises several nosological forms. The most prevalent phenotypes of CID are Leber hereditary optic neuropathy (LHON) and Leigh syndrome. In this study we have analyzed skin fibroblasts from 11 patients with mutations in mtDNA, which cause LHON or Leigh-like phenotypes (m.11778 G>A ( n = 3), m.3460 A>G ( n = 2), m.3635 G>A ( n = 1), m.3308 T>G ( n = 2), m.3472 T>C ( n = 1)), and 2 patients with earlier unknown substitutions m.3945 C>A and m.14441 T>C. High-resolution respirometry (HRR) was performed for complex analysis of the mitochondrial respiratory function in intact and permeabilized fibroblasts of patients and healthy controls. Flux control ratios in intact cells R/E, (R-L)/E were raised compared to the control. Rates of R, E, L normalized on the citrate synthase (CS) activity were statistically different ( p < 0.05) between patients and controls. In permeabilized fibroblasts we have found statistically significant differences ( p < 0.05) in ratios СII/E, Rot/E, R/CII, CI/CII between groups. These data highlight dysfunctions of the OXPHOS system, particularly CI. Increased CS activity and decreased CI/CII ratio suggest a compensatory metabolic response to the respiratory chain dysfunction. Our results show applicability of HRR in revealing biochemical abnormalities of mitochondrial complex I in fibroblasts of patients with LHON and Leigh-like syndrome. We also suggest HRR to be a useful method for inspection of new mutations causing mitochondrial complex I deficiency.